PENGARUH CELEBRITY ENDORSER’S CREDIBILITY TERHADAP SELF-BRAND CONNECTION DAN BRAND EVALUATION - PEBI PALENTINA; KLEMENS WEDANAJI PRASASTYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to know the impact of a celebrity endorsement’s credibility on a consumer self-brand connection and brand evaluation. In addition, it is also to testify the moderation on self-brand connection and brand evaluation. The technique uses Structural Equation Modelling along with AMOS 22 and purposive sampling. The results are celebrity endorser’s credibility impacts on self-brand connection and endorser brand fit moderates the relationship between them. However, celebrity endorser’s credibility and self-brand connection doesn’t impact on brand evaluation and there is no moderation between celebrity endorser’s credibility and brand evaluation.